2005
DOI: 10.4319/lo.2005.50.6.2022
|View full text |Cite
|
Sign up to set email alerts
|

Can feeding of fish on terrestrial insects subsidize the nutrient pool of lakes?

Abstract: We estimated consumption and excretion rates of terrestrial-borne phosphorus by a population of the insectfeeding fish species bleak (Alburnus alburnus) in a 0.12-km 2 mesotrophic lake of the German lowlands. Fish abundance, growth rates, and diet composition were determined, and consumption and nutrient metabolism were calculated by a bioenergetics model. Mean bleak abundance was about 77,000 ind. km Ϫ2. About 84% of bleak consumption consisted of terrestrial insects. Annual consumption of lake-external phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 48 publications
1
71
1
Order By: Relevance
“…comm., 2006) the same situation exists in Iberian rivers. Other factors that may contribute to the adaptability of the bleak include its ability to exploit a widespread spectrum of prey (Vollestad, 1985;Chappaz et al, 1987;Biro & Musko, 1995;Vasek & Kubecka, 2004;Mehner et al, 2005) and its temperature tolerance (from mountain lakes to the River Ebro with summer temperatures around 30ºC).…”
Section: Discussionmentioning
confidence: 99%
“…comm., 2006) the same situation exists in Iberian rivers. Other factors that may contribute to the adaptability of the bleak include its ability to exploit a widespread spectrum of prey (Vollestad, 1985;Chappaz et al, 1987;Biro & Musko, 1995;Vasek & Kubecka, 2004;Mehner et al, 2005) and its temperature tolerance (from mountain lakes to the River Ebro with summer temperatures around 30ºC).…”
Section: Discussionmentioning
confidence: 99%
“…4A). Kawaguchi and Nakano (2001) found that terrestrial insects contribute about 50% of the total annual prey consumption of salmonids in some Japanese streams, while about 84% of the consumption in a cyprinid (Alburnus alburnus) in a German lake comes from terrestrial sources (Mehner et al 2005). In the presence of artificial light near a waterbody, terrestrial insects could become an even more important food source for fish.…”
Section: Ecosystem Functioningmentioning
confidence: 99%
“…No conclusion can be drawn from the gill net catches about the habitat use of small perch during night after the pikeperch stocking because only two individuals were caught during two sampling occasions. In contrast, perch of all size classes were observed resting in high numbers in shallow littoral areas before and after the pikeperch stocking during night (Haertel et al 2002; T. Schulze, personal observations) and were not even caught with active fishing methods in the pelagic zone (purse seine) during night in the pikeperch period (H. Dörner, unpublished data; see Mehner et al (2005b) for details on fishing methods). This indicates a nearly exclusive inactive use of littoral habitats by small perch during night in the pikeperch period, whereas active perch were caught in both habitats during night in the pikeperch-free period.…”
Section: Abundance and Distribution Of Preymentioning
confidence: 99%